2011
DOI: 10.1523/jneurosci.4130-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Grafted Neural Progenitors Integrate and Restore Synaptic Connectivity across the Injured Spinal Cord

Abstract: Transplantation of neural progenitor cells (NPC) is a promising therapeutic strategy for replacing neurons lost following spinal cord injury, but significant challenges remain regarding neuronal integration and functional connectivity. Here we tested the ability of graft-derived neurons to reestablish connectivity by forming neuronal relays between injured dorsal column (DC) sensory axons and the denervated dorsal column nuclei (DCN). A mixed population of neuronal and glial restricted precursors (NRP/GRP) der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
178
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(186 citation statements)
references
References 45 publications
8
178
0
Order By: Relevance
“…Previous studies have demonstrated that NS/PC transplantation for SCI affects histological and/or functional outcomes in several processes, including neurotrophic support [32,33], angiogenesis [34,35], axonal regrowth [24,36], neural circuit reconstruction [37][38][39], and remyelination [40,41]. Most of these previous studies involved the use of rodent SCI models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that NS/PC transplantation for SCI affects histological and/or functional outcomes in several processes, including neurotrophic support [32,33], angiogenesis [34,35], axonal regrowth [24,36], neural circuit reconstruction [37][38][39], and remyelination [40,41]. Most of these previous studies involved the use of rodent SCI models.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, immunoelectron microscopy demonstrated the rafted cells could integrate the synaptic relay with host neuronal cells. The host-graft interactions of neuronal regeneration accelerated recovery [33,38].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have relied on gradients of neurotrophic factors to guide regenerating axons to correct brainstem regions, a technique that could equally lead axons astray if misplaced (5,20). Identifying therapies that encourage proper guidance is paramount to the goal of long-distance regeneration (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…cDNA was made with the SuperScript III CellsDirect cDNA synthesis kit (Life Technologies) and a mixture of Oligo(dT) 20 and random primers. qPCR was performed using the appropriate primer pair (Table S1) in a SYBR Green Master Mix (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…One major limitation of these techniques, however, is that it is not possible to determine whether these synaptic structures are functional. Electrophysiological techniques, routinely used to assess synaptic activity (Ramer et al, 2000;Bonner et al, 2011) would have been a superior assay of functional synapse formation. Previous findings suggest that the regeneration of dorsal column axons, for example, fails to produce a detectable electrophysiological response in the presence of readily detected synapses (Alto et al, 2009).…”
Section: Review Of Lu Et Almentioning
confidence: 99%